Subcloning of influenza a ha-na synthetic gene in bacterial system - Hassan, Marwa Noruddin Mahammad (Universiti Sains Malaysia, 2017)
Avian influenza A H5N1 virus continues to cause outbreaks around the globe since its first emergence in 1997 in Hong Kong. The highly pathogenic virus is capable of undergoing antigenic drifts and antigenic shifts as mechanisms enabling it to evade any immunity induced against it raising the alarm of potential pandemics and outbreaks. These mechanisms were found to influence two pathogenic determinants of Influenza A H5N1, which are the surface glycoprotein heamagglutinin HA and surface protein neuraminidase NA. These molecules are a principal target when it comes to vaccines production to eradicate the potentially deadly virus. In this project, highly immunogenic/hydrophilic regions of HA and NA were constructed and characterized through cloning. The synthetic gene HA-NA was successfully cloned where the assembling with the authentic synthetic gene sequence displayed 100 % similarity. The successfully cloned gene can be utilized for the production of highly immunogenic vaccine which is capable of producing sustainable immunity across generations of the virus, thus lightening the strain of producing annual vaccine in order to combat the newly arising variant. Additionally, it can be used as a tool to understand the immunogenic features of the hybrid gene which can assist in further understanding of the body mechanism in tackling the viral infections.